Self Empowerment Through Self Hypnosis : Harnessing the Enormous Potential of the Mind - Weschcke, Carl Llewellyn, 1930-2015 and Slate, Joe H. (Woodbury Llewellyn Publications, 2010)
Helps you tap into the unlimited power of your subconscious. This title lets you follow helpful scripts and practise easy techniques - involving trance, meditation, and sleep - to transform into the empowered person you're meant to be.
Includes Index Appendix, and Glossary.
Keywords: Autogenic Training